MINERALOGICAL AND GEOCHEMICAL CHARACTERIZATION OF THE ARIZLI MN DEPOSIT (AFYONKARAHISAR, TURKEY): EVIDENCE FOR DIAGENETIC AND SUPERGENE ENRICHMENT - Yalcin, Cihan; Kara, Hatice (Carpathian Assoc Environment and Earth Sciences, 2026)
The Ar & imath;zl & imath; Mn deposit (Afyonkarahisar, Turkiye) represents a diagenetic and supergene manganese mineralization system hosted within radiolarian chert-limestone alternations of an ophiolitic m & eacute;lange. X-ray diffraction (XRD) analysis confirms that the primary manganese minerals are pyrolusite (MnO2) and psilomelane [(Ba,H2O)(2)Mn5O10], with minor occurrences of quartz and calcite. Bulk geochemical analyses reveal MnO values ranging from 38.2 to 52.7 wt.%, with Mn/Fe ratios between 30 and 50, indicating enrichment in oxidized manganese. Trace element ratios, particularly Co/Zn and Ni/Co, suggest deposition under oxic conditions followed by diagenetic transformation and later-stage supergene enrichment. Discrimination diagrams-such as Fe2O3/TiO2 vs. Al2O3/(Al2O3+Fe2O3) and Co/Zn vs. Co+Ni+Cu-indicate that the deposit shares geochemical characteristics with supergene Mn accumulations in Iran, Morocco, and North China, while contrasting with hydrothermal Mn deposits found in Turkey and Pakistan. The mineralization is structurally concentrated in faulted boundaries between ophiolitic m & eacute;lange and Mesozoic carbonates, which enabled fluid migration and the remobilization of manganese. This paper introduces a comprehensive genetic model for supergene manganese deposits in ophiolitic environments, improves our comprehension of manganese metallogenesis in Tethyan ophiolitic belts, and suggests geochemical criteria relevant to the global exploration of manganese-rich sequences.
Keywords: Manganese mineralization; ophiolitic m & eacute;lange; diagenetic mineralization; supergene enrichment; geochemistry